Two cultures in the times of interdisciplinary archaeology. A response to commentators. (June 2019) - Arponen, V. P. J.; Dörfler, Walter; Feeser, Ingo; Grimm, Sonja; Groß, Daniel; Hinz, Martin; Knitter, Daniel; Müller-Scheeßel, Nils; Ott, Konrad; Ribeiro, Artur
Abstract : We would like to begin by thanking the journal and the commentators for their time and attention.